Kualitas Pelayanan Electronic Library pada UPT Perpustakaan Universitas Pendidikan Ganesha - Dewantari, Ni Luh Wahyuni; Sujana, I Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2022)
This research aim to determine the Electronic Library service quality at the UPT of the Ganesha Education University Library, seen from the dimensions of Affect of Service, Information Access, Library as Place, and Personal Control. The research type in this study is a descriptive research type. This research population is students who are members of the Ganesha University of Education library. The research sample was determined by accidental sampling technique as many as 387 orangts. Using the questionnaire method in data collection. Meanwhile, the data analysis technique used descriptive analysis. The results of this study indicate that the service quality of the Electronic Library at the UPT of the Ganesha University of Education Library generally has a good service assessment, however, there are still several aspects that need to be addressed related to the availability of reading material in the library or the Electronic Library services and inadequate infrastructure.